GFAP as a marker of reactive astrocytes in the mice brain following hemorrhagic stroke and HSV-I - Gumenyuk, A.V.; Rybalko, S.L.; Savosko, S.I.; Guzyk, M.M.; Tykhomyrov, A.O.; Ryzha, A.A.; Chaikovsky, Yu.B. (Вiopolymers and Cell, 2017)
Aim. To investigate reactive changes of GFAP-positive astrocytes as a marker of brain response following hemorrhagic stroke and HSV-I. Methods. The experiments were performed on 110 Balb/c mice weighing 18–20 g. The animals were infected with HSV type I, on 30 day hemorrhagic stroke was simulated and changes in astrocytes were determined by immunohistochemistry. Gliosis was confirmed by changes in density and arborization of GFAP-positive astrocytes. Results. The results of immunohistochemical studies confirmed increased density of GFAP-positive astrocytes in the hippocampus of mice infected with HSV type I as well as the sharp increase in the density and hypertrophy of GFAP-positive astrocytes following stroke simulation in infected animals. Conclusions. The experiment has provided new evidence about the location and level of astrocytic gliosis following a stroke and herpes infection. GFAP can be studied as a marker of HSV type I reactivation against stroke. Мета. Дослідити зміни GFAP-позитивних астроцитів як прояв їх реактивних змін у відповідь на пошкодження мо-зку при геморагічному інсульті та ВПГ-І. Методи. Проведено експерименти на 110 білих мишах Balb/c масою 18–20 г. Тварин інфікували ВПГ-І, на 30 добу моделювали геморагічний інсульт і визначали зміни астроцитів методом імуногістохімії. Гліоз визначали за щільністю та арборизацією відростків GFAP-позитивних астроцитів. Результати. Результати імуногістохімічного дослідження засвідчили збільшення щільності GFAP-позитивних відростків астроцитів у гіпокампу мишей інфікованих ВПГ-І, а після моделювання інсульту у інфікованих тварин різке збільшення щільності і гіпертрофію GFAP-позитивних астроцитів. Висновки. В експерименті отримано нові дані щодо локалізації та рівня астроцитарного гліозу при інсульті та герпетичній інфекції. GFAP можна розглядати як маркер реактивації ВПГ-І на тлі інсульту. Цель. исследовать изменения GFAP-позитивных астроцитов как проявление их реактивных изменений в ответ на повреждение мозга при геморрагическом инсульте и ВПГ-I. Методы. Проведены эксперименты на 110 белых мы-шах Balb/c массой 18–20 г. Животных инфицировали ВПГ-I, на 30 сутки моделировали геморрагический инсульт и определяли изменения астроцитов методом иммуногистохимии. Глиоз определяли по плотности и арборизации отростков GFAP-позитивных астроцитов. Результаты. Результаты иммуногистохимического исследования показа-ли увеличение плотности GFAP-позитивных отростков астроцитов в гиппокампе мышей инфицированных ВПГ-I, а после моделирования инсульта у инфицированных животных резкое увеличение плотности и гипертрофию GFAP-позитивных астроцитов. Выводы. В эксперименте получены новые данные по локализации и уровню астро-цитарного глиоза при инсульте и герпетической инфекции. GFAP можно рассматривать как маркер реактивации ВПГ-I на фоне инсульта.